Cash and Financial Constraints: An Empirical Analysis of Non-Financial Firms Listed in Indonesian Stock Exchange 2005-2014 - Sigit S. Wibowo; Stefany Lolyta (Sebelas Maret Business Review, 2016)
This study examines corporate motives to hold cash and its equivalents as forms of financing, by using non-financial public firms listed in Indonesian Stock Exchange (IDX) between 2005 and 2014. Three criteria are employed to distinguish constrained and non-constrained firms namely: KZ index, dividend payment, and firm size. Based on the results of PLS, this study finds that the amount of cash holding is increasing along with the increase of cash flows. This result is consistent for both firm categories based on the previous criteria. However, based on the 2SLS method, cash flow does not affect the cash holdings of the firms with financial constraints. The result of this research shows that firms with financial constraints have strong motivation to hold cash due to lack of access to external financing.